2017
DOI: 10.1111/jcap.12191
|View full text |Cite
|
Sign up to set email alerts
|

Improving the culture of safety on a high‐acuity inpatient child/adolescent psychiatric unit by mindfulness‐based stress reduction training of staff

Abstract: A brief MBSR training program offered to an interprofessional staff of a high-acuity inpatient adolescent psychiatric unit was effective in decreasing their stress, increasing their mindfulness, and improving staff and patient safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 20 publications
0
14
0
1
Order By: Relevance
“…Of note, one study reported a reduction in stress on the Depression Anxiety Stress Scale (Lovibond and Lovibond 1995 ), but a non-significant finding on the Perceived Stress Scale (Cohen et al 1983 ; Duchemin et al 2015 ). Significant reductions in stress were also maintained ranging from 2 months (Hallman et al 2017 ) to 1-year (Geary and Rosenthal 2011 ) follow-up. However, significant reductions in stress were not maintained at 3-month follow-up (Ducar et al 2019 ; Suyi et al 2017 ) and 6-month follow-up (Ducar et al 2019 ).…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Of note, one study reported a reduction in stress on the Depression Anxiety Stress Scale (Lovibond and Lovibond 1995 ), but a non-significant finding on the Perceived Stress Scale (Cohen et al 1983 ; Duchemin et al 2015 ). Significant reductions in stress were also maintained ranging from 2 months (Hallman et al 2017 ) to 1-year (Geary and Rosenthal 2011 ) follow-up. However, significant reductions in stress were not maintained at 3-month follow-up (Ducar et al 2019 ; Suyi et al 2017 ) and 6-month follow-up (Ducar et al 2019 ).…”
Section: Resultsmentioning
confidence: 89%
“…However, non-significant findings were also reported for the facet observe (Dobie et al 2016 ), describe (Manotas et al 2014 ; Martin-Asuero et al 2014 ), acting with awareness and non-reactiveness (Manotas et al 2014 ). In terms of follow-up, significant improvements in mindfulness were observed ranging from 2 months (Hallman et al 2017 ) to 3 months (Brady et al 2012 ; Ducar et al 2019 ; Schroeder et al 2016 ; Suyi et al 2017 ). However, in several studies significant improvements in mindfulness were not maintained at 3 (Wang et al 2017 ) or 6 months (Ducar et al 2019 ; Wang et al 2017 ) follow-up.…”
Section: Resultsmentioning
confidence: 99%
“…Just as adolescents need to feel safe and contained, clinicians have similar needs. The more clinicians had a sense of a structured pathway and model for providing care, they appeared to feel secure and confident in their work, in turn this is helpful for adolescents in creating a safe environment (Hallman et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The culture of any organization is crucial to how it operates and functions (Davis & Cates, 2018;Garcia et al, 2017). Studies of adolescent inpatient units have focused on the importance of culture models in improving quality of care (Hallman, O'Connor, Hasenau, & Brady, 2017;Slemon, Jenkins, & Bungay, 2017;Vella et al, 2017). Regan et al (2017) reported that to create a therapeutic milieu, a philosophy of care needs to be established to guide the culture and structure of the unit.…”
Section: Discussionmentioning
confidence: 99%
“…The article by Hallman, O'connor, Hasenau, and Brady () is a good complement to strategies for building a positive unit culture and reducing coercive measures. In inpatient units, support is bidirectional.…”
mentioning
confidence: 99%